Manual de implantação de serviço de terapia nutricional para hospital oncológico - Pinheiro, Felipe José Frade [UNIFESP] (2019)
Introduction: Cancer is a catabolic disease that consumes the patient's nutritional reserves due to increased energy expenditure due to the present tumor activity, with malnutrition being the main nutritional complication in these patients. Objective: Develop and validate a manual for the implantation of a nutritional therapy service in an oncology hospital. Method: Study approved by the Ethics and Research Committee of the Federal University of São Paulo with opinion number 3,354,094 / 2019. This is a descriptive study on the development and validation of a manual, carried out in phases: search for anteriority, bibliographic survey to support the construction of the manual, content development, validation with expert judges using the Delphi Technique and an instrument of evaluation, in which the Content Validity Index was used. The manual was published in e-book format. Results: The validation with expert judges reached a Content Validity Index of 1.0, therefore the global Content Validity Index was also equal to 1.0, reaching a total agreement index in the first evaluation round. The manual presents information on the composition and performance of the Multidisciplinary Nutritional Therapy Team and on nutritional assessment, which involves elements of dietary, anthropometric, physical and biochemical assessment. It also presents the calculation of nutritional needs, the nutritional care plan and will monitor clinical and quality indicators in nutritional therapy. Conclusion: A Manual for the Implementation of a Nutritional Therapy Service for Hospital Oncology was developed and validated.